Neurological Manifestations of Autosomal Dominant Alzheimer’s Disease from the DIAN cohort and a meta-analysis - Tang, Mengxuan (Lancet Neurol, 2016)
BACKGROUND: To evaluate the prevalence rates of non-amnestic neurological symptoms of autosomal dominant Alzheimer’s disease (ADAD) in the DIAN Observational Study (DIAN–OBS) and the published literature. Analyses were conducted to clarify the prevalence of neurological manifestations of ADAD mutation carriers as a group. METHODS: Using the DIAN-OBS study database and 189 peer-reviewed publications on ADAD families, we extracted individual-level data on age of symptom onset, disease course from onset to death, and the presence of fourteen neurological findings that have been reported in association with ADAD and included symptomatic subjects only. The primary outcomes were the rates of various neurological symptoms and the contribution of age and specific mutations on the prevalence of the neurological symptoms. Analyses were done using descriptive statistics, comparisons of means and frequencies and multivariable linear regression. FINDINGS: Our meta-analysis dataset includes 1228 affected individuals, with detailed clinical descriptions of 753. The DIAN–OBS dataset included 107 individuals with detailed clinical data. The most prevalent non-amnestic cognitive manifestations in DIAN were those typical of mild-moderate Alzheimer’s disease, including visual agnosia (95% CI 45·7%–64·6%), aphasia (43·8%–62·7%), and behavioral changes (51·5%–70·0%). The prevalence of non-amnestic cognitive manifestations from the published literature were (95% CI 3·9%–7·2%) for visual agnosia, (20%–26%) for aphasia, and (28·4%–35·1%) for behavioral changes. Prevalence of non-cognitive neurological manifestations in DIAN was low, including myoclonus and spasticity (3·8%–15·0%), seizures (0·5%–9·1%) and moderate for parkinsonism (5·3%–17·1%). Whereas, in the published literature the prevalence was (95% CI 16·6%–22·2% and 12·5%–17·6%) for myoclonus and spasticity, (10·1%–15·0%) for parkinsonism, and (17·4%–23·2%) for seizures. Age of onset appears to influence the prevalence of several non-cognitive manifestations in both groups, stroke being more prevalent at older ages of onset with motor symptoms being more prevalent at younger age of onset and at an older age of onset. Further, symptoms were overall more common in later clinical stages of disease. INTERPRETATION: Comparing the prevalence of non-amnestic and non-cognitive clinical features in DIAN with the published literature indicates that previous reports of non-cognitive features are likely overestimated whereas DIAN identifies higher non-amnestic cognitive symptoms in addition to memory impairment. The non-cognitive clinical manifestations of AD appear to be in a minor fraction of mild-moderate ADAD and is likely influenced by disease severity, environmental and genetic factors in addition to genetic status. The results of this work clarify the clinical presentations of ADAD including the effects of age and disease stage. Attention to these neurologic symptoms and screening for ADAD mutations are warranted if present. Future work is needed to determine the factors which cause these neurologic symptoms.